2021
DOI: 10.53625/ijss.v1i3.406
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Capital Structure, Liquidity and Profitability on Company Value in the Food Sub Sector and Beverages on the Indonesia Stock Exchange

Abstract: This research is motivated by the inconsistency of the results of previous studies so that the purpose of this study is to determine the effect of capital structure, liquidity and profitability on firm value in the Food and Beverage Sub-Sector on the Indonesia Stock Exchange in 2016-2019. The population in this study is the Food and Beverage Sub-Sector companies on the Indonesia Stock Exchange in 2016-2019 through the website www.idx.co.id, where the sample used is 12 companies with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 1 publication
0
0
0
Order By: Relevance
“…Several researchers found that the capital structure has a positive impact to the firm value (Suzulia and Saluy, 2020;Purwanti, 2020;Rahmawati et al, 2021). And other studies found that the capital structure affects negatively and/or is not significant to the firm value (Antoro et al, 2020;Yasin and Studiviany, 2021;Rudini et al, 2021;Halfiyyah and Suriawinata, 2019).…”
Section: Introductionmentioning
confidence: 93%
See 3 more Smart Citations
“…Several researchers found that the capital structure has a positive impact to the firm value (Suzulia and Saluy, 2020;Purwanti, 2020;Rahmawati et al, 2021). And other studies found that the capital structure affects negatively and/or is not significant to the firm value (Antoro et al, 2020;Yasin and Studiviany, 2021;Rudini et al, 2021;Halfiyyah and Suriawinata, 2019).…”
Section: Introductionmentioning
confidence: 93%
“…Previous studies that found the capital structure has a positive impact to the firm value are (Suzulia and Saluy, 2020), (Anggraeni and Haryani, 2020), (Purwanti, 2020), (Rahmawati et al, 2021). Meanwhile the studies written by (Halfiyyah and Suriawinata, 2019), (Sutanto et al, 2019), (Antoro et al, 2020), (Yasin and Studiviany, 2021), (Rudini et al, 2021), (Wijayaningsih and Yulianto, 2021) stated that the capital structure has negative impact/not significant to the firm value. And the hypothesis that could be arranged regarding capital structure to the firm value are: H1: Capital Structure has a positive and significant effect on firm value.…”
Section: Theoretical Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…Karena belum mencapai titik optimalnya, manfaat yang diterima dari peningkatan kewajiban lebih besar dari pengorbanan yangg dikeluarkan mengakibatkan manfaat dalam pemakaian kewajiban dari jangka panjang maupun pendek dapat meningkatkan nilai sebuah perusahaan (Amro & Asyik, 2021). Hasilnya sesuai penelitian Rosalia et al, (2022) tetapi bertentangan penelitian Ni Wayan Rudini et al, (2021) struktur modal tidak mempengaruhii nilai perusahaan…”
Section: Pengaruh Struktur Modal Terhadap Nilai Perusahaanunclassified